Facial Synthesis of 1T Phase MoS2 Nanoflowers via Anion Exchange Method for Efficient Hydrogen Evolution. Issue 7 (15th February 2019) - Li, Jinming; Qi, Weihong; Li, Yejun
Abstract: In this work, a low cost and high yield method is proposed to synthesize 1T phase MoS2 nanoflowers (NFs) by means of anion exchange using MoO3 nanosheets as the exchange template. The synthesized MoS2 NFs are composed of ultrathin MoS2 nanoflakes with plenty of active edge sites, large specific surface area, and rich defects, as well as reduced intrinsic resistance. Therefore, they show enhanced hydrogen evolution reaction (HER) activity with an overpotential of 166 mV at 10 mA cm −2 and Tafel slope of 47 mV dec −1, better than those of previously reported MoS2 ‐based HER catalysts. A systematic study is carried out on the effects of mass loading and reaction temperature on its catalytic performance. It is shown that, with reaction temperature of 200 °C and mass loading of 0.43 mg cm −2, the obtained MoS2 NFs show the optimal HER activity. The present work provides a facile and cost‐effective way to synthesize 1T MoS2 NFs with advanced HER performances, indicating significant potential for larger‐scale production in practical industrial applications. Abstract : 1T phase MoS2 nanoflowers (NFs) were synthesized by means of anion exchange using MoO3 nanosheets as the template. The synthesized MoS2 NFs are composed of ultrathin MoS2 nanoflakes with plenty of active edge sites, large specific surface area, and rich defects, as well as reduced intrinsic resistance. Therefore, they show enhanced hydrogen evolution reaction (HER) activity. The present work provides a facile and cost‐effective way to synthesize 1T MoS2 NFs with advanced HER performances, indicating significant potential for larger‐scale production in practical industrial applications.